Analisis Pengaruh Kualitas Sistem Media Elektronik E-Filling dan E-Billing Terhadap Tingkat Kepuasan Wajib Pajak (Studi Pada Wajib Pajak di Fakultas Ekonomi Universitas Tridinanti Palembang) - Dimas Pratama Putra; Padriyansyah (Fakultas Ekonomi Dan Bisnis Universitas Pancasila, 2019)
This research is being done to taxpayers at economic faculty of Tridinanti Palembang. This research aims to know effect the quality of the e-filing and e-billing system toward taxpayers satisfaction level. The population in this study is 339 taxpayers. Sample of 130 taxpayers by using purposive sampling methods. The analytical technique used is a descriptive analysis and conducted a asumsi klasik test. The result of this study is (1). The quality of the e-filing system has a significant positive effect on the degree of taxpayers satisfaction, (2). The quality of the e-filing system has a significant negative effect on the degree of taxpayers satisfaction, dan (3). The quality of e-filing and e-billing system collectively has a significant positive effect on the rate of taxpayers satisfaction.